PENGARUH EDUKASI TENTANG STUNTING TERHADAP TINGKAT PENGETAHUAN PADA IBU DI DUSUN XIII/DAHLIA DESA BANDAR KHALIPAH - Harefa Rahmat Nezer; Silaen Harsudianto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
According to the World Health Organization (WHO, 2021), 148.1 million children under the age of 5 are too short for their age (stunting), 45.0 million are too thin for their height (wasting), and 370 million are too heavy for their height (overweight). Previous research shows that families with stunted children are usually caused by a lack of knowledge of parents, especially mothers. The purpose of this education is to prevent stunting by providing health education about stunting to parents who have small children. The research design in this study is that the researcher used a quantitative form of research, the research design used was a design with a type of pre-experimental desings. and using the one group pretest - posttest design method, the sample used in this study was 22 people and used the total sampling technique. after testing using a non-parametric test (wilcoxon signe ranks test) shows the results of the Z-score of (-4,132) > 1.96 for α = 0.05, which means that there is an effect of education about stunting on the level of knowledge of mothers in hamlet xiii / dahlia village bandar khalipah. It is recommended for future researchers to add or replace variables, feeding behavior, parental roles, parental attitudes, community awareness, research can provide a comprehensive picture of the factors that support individuals to overcome stunting.